Implementation of Information and Communications Technology at Naval State University - Reymark Pabilando; Ernald M. Du (Inclusive Society and Sustainability Studies, 2022)
This study primarily aimed to evaluate the implementation of Information and Communications Technology at Biliran Province State University. The descriptive-correlational design was used to gather data on the profile of the faculty, technological competencies of the faculty, the extent of implementation of ICT at Biliran Province State University, problems encountered by the faculty in the implementation of ICT, and the feedbacks of the faculty in the implementation of ICT at Biliran Province State University during the school year 2017-2018. Most of the faculty are middle-aged, females, non-ICT, has a length of service of 5 years and below, has mastered units, and has not attended training in ICT. The faculty has the competencies to use the technology for productivity, research, communication, presentation, and media purposes. On the other hand, there is a significant relationship between the technological competencies of the faculty and the extent of implementation of ICT, and between the problems encountered by the faculty in the implementation of ICT and the extent of implementation of ICT. It is concluded that the ICT was often implemented by the faculty in Biliran Province State University. It is hereby recommended that the training plan crafted by the researcher should be utilized to improve the teaching competencies of the faculty in the utilization of ICT at Biliran Province State University.